2005
DOI: 10.1042/bj20040966
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of denatured collagen into hepatic stellate cells: evidence for the involvement of urokinase plasminogen activator receptor-associated protein/Endo180

Abstract: Tissue remodelling is dependent on the integration of signals that control turnover of ECM (extracellular matrix). Breakdown and endocytosis of collagen, a major component of the ECM, is central to this process. Whereas controlled secretion of matrix-degrading enzymes (such as matrix metalloproteinases) has long been known to mediate ECM breakdown, it is becoming clear that uPARAP/Endo180 (where uPARAP stands for urokinase plasminogen activator receptor-associated protein) serves as a receptor that mediates en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…DDR receptors regulate cell adhesion, migration, proliferation, and remodeling of the extracellular matrix by controlling the expression and activity of MMPs (42,55). Similarly, uPARAP/Endo180 from the mannose receptor family was found to be important for collagen internalization in activated rat HSCs (37) and other cultured cells (12,29,33,37,51). Our study provides evidence that collagen macropinocytosis is an additional communication mechanism between HSCs and extracellular matrix.…”
Section: C628mentioning
confidence: 66%
See 1 more Smart Citation
“…DDR receptors regulate cell adhesion, migration, proliferation, and remodeling of the extracellular matrix by controlling the expression and activity of MMPs (42,55). Similarly, uPARAP/Endo180 from the mannose receptor family was found to be important for collagen internalization in activated rat HSCs (37) and other cultured cells (12,29,33,37,51). Our study provides evidence that collagen macropinocytosis is an additional communication mechanism between HSCs and extracellular matrix.…”
Section: C628mentioning
confidence: 66%
“…In liver, HSCs are important not only for collagen production that contributes to liver cirrhosis, but also for collagen degradation during cirrhosis resolution. Collagen has been reported to be internalized by macrophages and fibroblasts (1,30) and recently by HSCs (36,37). However, the mechanisms and relevance of this process remain undefined and were the focus of this investigation.…”
mentioning
confidence: 99%
“…A member of the mannose receptor family, uPARAP is expressed on macrophages and mesenchymal cells, including chondrocytes and some fibroblasts (Howard et al 2004;Sheikh et al 2000). Mesenchymal cells that lack uPARAP are unable to internalize collagen (Curino et al 2005;East et al 2003;Engelholm et al 2003;Kjoller et al 2004;Madsen et al 2007;Mousavi et al 2005). In addition to its role in collagen internalization and degradation, uPARAP contributes to the adhesion and migration of collagen in vitro (Engelholm et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for the lack of lung phenotype is use of an alternative pathway for collagen internalization. Although previous work demonstrated that uPARAP was the primary receptor for collagen internalization in dermal fibroblasts and mouse embryonic fibroblasts (3,(7)(8)(9), other studies have implicated integrins (specifically, a2b1) and MMPs for collagen internalization in different cells (10,11). Therefore, we asked whether lung fibroblasts required uPARAP for collagen internalization.…”
mentioning
confidence: 99%